How Good is Family Therapy? A Reassessment - Roy, Ranjan (Book collections on Project MUSE., 1995)
Family therapy is one of the most widely practised psychotherapies in North America. Roy and Frankel here provide a comprehensive and critical reassessment of the research literature regarding the efficacy of this form of treatment. The main thesis of the book is that this research is still in its infancy and that, although important contributions have been made, much work remains to be done.